Music interventions in disorders of consciousness (DOC) - a systematic review - Grimm, Teresa; Kreutz, Gunter (Brain injury, 2018)
The effects of music interventions including active and receptive music therapy for people living with neurogenic disorders of consciousness (DOC) have been subject to empirical studies in the past. The aim of this systematic review was to find and analyse the current research about the effects of musical interventions on people with DOC. For this purpose, studies with music interventions and patients with DOC from the year 1900 to 2017 were searched in English, German, and French in different databases. Risk-of-bias-analyses were conducted for each study that fulfilled the inclusion criteria. Twenty-two quantitative studies (three randomised controlled trials with more than 10 participants) were found eligible for review. They include a total of 329 participants living with either coma, unresponsive wakefulness syndrome, or minimally conscious state. Music interventions were associated with favourable behavioural and physiological responses in several studies, but methodological quality and outcomes were heterogeneous. More studies with a larger number of participants are needed as well as a consensus on key characteristics of effective short-term and long-term music interventions for DOC.